Woodland creation: monitoring natural processes and hybrid approaches - Burton, Vanessa; the TreE PlaNat project (My University, 2025)
Creating new woodlands via natural processes or hybrid methods that combine planting and natural processes can be a great way to support nature recovery and reduce resource use (e.g. reduced need for nursery tree production, tree protection etc). However, the process is highly variable and keeping an eye on how things are going will help to ensure the woodland is developing as you intended. The method described here allows land managers, volunteers or any other interested parties to survey sites to collect robust data on the progress of natural processes regardless of experience level. The method is flexible to fit the surveyors’ objectives and allows for comparisons over time providing it is carried out the same way at each time point. This method was developed by academics working on the TreE PlaNat project and reviewed the the Knowledge User Board.
Keywords: woodland creation; natural colonisation; natural regeneration; natural processes; tree planting; hybrid approaches; forest restoration